(untitled) (Collection of research papers «ECONOMIC STRATEGY AND PROSPECTS OF TRADE AND SERVICES SECTOR DEVELOPMENT», 2026)
The article examines the specific features of the functioning of the agro-industrial complex of Ukraine under conditions of wartime uncertainty and determines the role of transformational processes in logistics and digitalization in ensuring the efficiency of food systems. The relevance of the topic is determined by increasing risks for agricultural production, disruptions of logistics chains, destruction of transport infrastructure, and the need to adapt the agricultural sector to new socio-economic conditions. Under such circumstances, the search for innovative mechanisms to improve the efficiency of agricultural resource management and ensure the stability of food systems becomes particularly important. The purpose of the study is to substantiate the role of digital transformation and logistics innovations as key instruments for improving the efficiency of the agro-industrial complex of Ukraine, forming resilient food supply chains, and ensuring national food security. In the course of the research, general scientific and special methods were used, including the systemic approach, analysis and synthesis, economic and statistical analysis, comparative analysis, as well as the generalization of scientific publications and statistical data from international organizations. The results of the study demonstrate that the digitalization of the agricultural sector creates new opportunities for increasing the efficiency of the use of land, material, and energy resources. The use of precision farming technologies, geographic information systems, agricultural drones, Internet of Things-based monitoring systems, and big data analytics allows the optimization of production processes, increases agricultural productivity, and reduces resource consumption. At the same time, digital logistics management platforms and electronic trading platforms contribute to the formation of more transparent and efficient supply chains for agricultural products, expand producers’ access to domestic and international markets, and reduce transaction costs. It is proven that the development of digital infrastructure and the implementation of innovative technologies in the agricultural sector contribute to the formation of more resilient agri-food systems capable of functioning effectively under conditions of economic and wartime instability. Digitalization of logistics processes enables real-time monitoring of product movement, optimization of transport routes, improvement of supply chain transparency, and reduction of food losses during transportation and storage. The study also confirms that the digital transformation of the agro-industrial complex plays an important role in ensuring food security, as it contributes to increasing the stability of production, improving the efficiency of food resource distribution, and enhancing the accessibility of food products for the population. Furthermore, the introduction of digital technologies corresponds to the principles of sustainable development, as it promotes rational use of natural resources, reduces environmental pressure on agricultural ecosystems, and increases the energy efficiency of production processes. The practical significance of the obtained results lies in identifying promising directions for the digital transformation of the agro-industrial complex of Ukraine, which will contribute to increasing the competitiveness of the agricultural sector, strengthening food security, and forming resilient agri-food systems in the context of implementing the concept of sustainable development. The scientific novelty of the research lies in the comprehensive substantiation of the interconnection between the digital transformation of the agricultural sector, the development of logistics systems, and the provision of food security in Ukraine under conditions of wartime and economic uncertainty.